Application of vortex granulators in technology of Ammonium Nitrate obtaining: Main advantages and environmental aspects of implementation - Artyukhov, Artem (2015)
An article deals with the application of vortex granulators in technology of ammonium nitrate obtaining. The review of the main methods of granulation is carried out. The basic advantages of suspended layer granulators are presented. The basic methods of intensification of heat and mass transfer processes during the granulation in weighted layer granulators are shown. An article presents a short description of the modern vortex type granulation equipment and its main disadvantages. An article describes the problem of waste management in the production of ammonium nitrate. A description of the main methods of waste utilization in production of ammonium nitrate (flue gas and substandard granules of ammonium nitrate) by using vortex granulators is presented. Separate class of weighted layer granulator is the vortex granulators with variable cross-sectional area of the working space. Environmental benefits of such devices are the possibility of classifying the granules in the working volume and internal circulation of small granules. The main advantages of the original constructions of suspended layer vortex granulators are presented. These advantages reduce the amount of small fraction granules and ammonium nitrate dust.